2005
DOI: 10.1111/j.1600-9657.2004.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oral trauma in children with bilateral clefts

Abstract: The main object of this study is to analyze the prevalence of oral trauma in subjects with complete bilateral clefts, with anterior projection of the premaxilla. A total of 106 children aging 6 months to 9 years were analyzed. The caretakers answered a specific questionnaire, in order to report the presence or absence of trauma to the soft and/or hard tissues of the child's mouth. Whenever there was a history of trauma, the patients were submitted to clinical examination. The prevalence of oral trauma was 53%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…5,6 Some authors stated that untreated premaxillary segments may lead to serious problems such as lack of proper anterior occlusion, segment mobility compromising articulation, and oronasal fistulae jeopardizing the maintenance of oral hygiene. 7 While soft tissue and dental trauma in children with protruded premaxillae have been reported in the literature, 1 fractures of the vomero-premaxillary junction seem to be rare.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…5,6 Some authors stated that untreated premaxillary segments may lead to serious problems such as lack of proper anterior occlusion, segment mobility compromising articulation, and oronasal fistulae jeopardizing the maintenance of oral hygiene. 7 While soft tissue and dental trauma in children with protruded premaxillae have been reported in the literature, 1 fractures of the vomero-premaxillary junction seem to be rare.…”
Section: Discussionmentioning
confidence: 99%
“…Complete bilateral cleft lip and palate (BCLP) patients show a characteristic anterior projection of the premaxilla which often persists even after lip repair. 1 This anatomical feature in BCLP children together with an increased overjet predisposes this region to trauma. Silva et al 1 found that 53% had suffered from oral trauma in their sample of 106 BCLP children, the majority sustained soft tissue lesions (91%) and dental trauma including avulsion, luxation, and intrusion of teeth were observed in the rest.…”
mentioning
confidence: 99%
See 3 more Smart Citations